Quality of antenatal care services received by women of reproductive age prior to delivery in selected public health facilities in the northern zone of Ghana - Michael Boah; Emmanuel Akolgo Abanga; Martin Nyaaba Adokiya (BMC, 2024)
Abstract Background Over the past two decades, antenatal care (ANC) coverage has increased in most settings across low- and middle-income countries, including Ghana. However, evidence shows that there is a need to focus on both access and quality to improve maternal and newborn health outcomes. We investigated ANC quality among public healthcare facilities in the northern region of Ghana. Methods We conducted a facility-based study involving 420 postpartum women, selected randomly from five public health facilities. We collected information on a set of prenatal services that respondents self-reported to have received during their most recent pregnancy. Women who received all the interventions assessed were considered to have received quality ANC. Using multilevel (mixed-effects) regression analysis, we identified the independent factors associated with ANC quality, with healthcare facility as the cluster variable. Results Of the 420 women, 31.2% (95% CI: 26.9, 35.8) received ANC services of high quality. ANC quality differed significantly by women's background characteristics and ANC use. However, gestational age at first ANC and the number of follow-up visits before delivery were significantly associated with ANC quality: booking the first visit in the second or third trimester reduced the odds of receiving high-quality ANC compared to booking in the first trimester (aOR = 0.15, 95% CI: 0.07, 0.31, and aOR = 0.09, 95% CI: 0.01, 0.83, respectively). In contrast, achieving a minimum of eight ANC follow-ups before delivery increased the odds of receiving high-quality ANC compared to attaining fewer than eight visits (aOR = 4.82, 95% CI: 2.33, 9.99). Conclusions A significant proportion of pregnant women in the study setting received suboptimal quality ANC during their most recent pregnancy. ANC quality was primarily associated with the timing of the first visit and the number of follow-up visits before delivery. Timely initiation of ANC and frequent follow-up visits will be crucial in the study's setting for pregnant women to benefit from comprehensive ANC services.